Make bottom number same
ok, so remember
(a-b)(a+b)=a²+b²
so
to get from (y-x) to (y²-x²), multiply 2nd fraction by (y+x)
so multiply 2nd fraction by (y+x)/(y+x)
![\frac{2x}{y^2-x^2}- \frac{(y+x)(x)}{y^2-x^2}](https://tex.z-dn.net/?f=%20%5Cfrac%7B2x%7D%7By%5E2-x%5E2%7D-%20%5Cfrac%7B%28y%2Bx%29%28x%29%7D%7By%5E2-x%5E2%7D%20%20)
=
![\frac{2x-x(x+y)}{y^2-x^2}](https://tex.z-dn.net/?f=%5Cfrac%7B2x-x%28x%2By%29%7D%7By%5E2-x%5E2%7D)
=
Not too sure what you're asking, but...
3(x+2) is the expression
Answer:45
Step-by-step explanation:
Key Word:of
30*2/3 = 45
Answer:
30
Step-by-step explanation:
Well we know the first angle is 90 degrees, which means we have 90 degrees left to work with. Then, the top angle would be 60 degrees, because there is a straight line (which of course has to equal 180), so 180-120 = 60. Now, 90-60=30!